Building a culture of learning at scale: learning networks for systems change. - McKenzie, Fiona (Orange Compass & Paul Ramsay Foundation, 2021)
This scoping paper explores the question ‘what would it take to build a culture of learning at scale?’. It focuses on systems-wide learning that can help to inform systems change efforts in complex contexts. To answer this question, literature was reviewed from across diverse disciplines and the realms of education, innovation systems, systems thinking and knowledge management. This inquiry was also supported by in-depth interviews with numerous specialists from the for-purpose sector and the examination of several case studies of learning across systems. The goal was to derive common patterns to inform a ‘learning for systems change’ framework. Learning for systems change is critical when working with complexity. The dynamic nature of complex adaptive systems requires an ability to continually sense and learn from the system and adapt accordingly. This is because the nature of the challenge and ‘what works’ to meet the challenge is continually shifting (Lowe and Plimmer, 2019). This requires an ongoing process of iterative inquiry that draws upon wisdom and insights from across the system. Such learning challenges traditional siloes of expertise and organisational boundaries (Clarke et al., 2019). Learning is not simply a nice to have. It is critical for greater impact and improved outcomes, particularly in mission-driven organisations and initiatives (Price et al., 2019). In this paper, a ‘learning networks’ approach is proposed, one that draws upon individual, group and systems-wide learning to build capacity and resilience for systems change in uncertain environments. This fills a gap in the literature where the focus is largely on learning within organisations. Instead, the focus here is on what is required to support learning to occur across scales and boundaries - from the individual to system-wide. A simple meta-framework for developing learning networks is proposed that includes high level guidance on the enabling conditions - the mindsets, relationships, processes and structures- that would enable learning networks to flourish.

Disentangling Government Responses: How Do We Know When Accountability Work is Gaining Traction? - Fox, Jonathan; Halloran, Brendan; Fölscher, Alta; McGee, Rosie (Accountability Research Center, 2024)
Advocacy for public accountability aims to produce certain reactions from government officials or service providers. However, the reactions can be many and diverse, and it is not always clear to advocates how to interpret them and decide on next steps—whether to intensify efforts or back off; continue the same strategy or make adjustments. This paper presents a framework to help accountability advocates and practitioners interpret government reactions to their efforts and move forward appropriately. The framework arises from learning and reflection in the context of the International Budget Partnership (IBP)’s Strengthening Public Accountability with Results and Knowledge (SPARK) program. SPARK seeks to bolster the collective agency of marginalized communities and coalitions to advance democratic and equitable fiscal governance systems that channel public resources to services that address the priority needs of these historically excluded groups. The paper: · unpacks the broad umbrella category of government responses to citizen-led accountability initiatives, discerning within it three overlapping categories of responses, responsiveness, and accountable responsiveness (RRA), and pinpointing what distinguishes them; · maps out the public financial management (PFM) system as the critical conduit for any public service to progress from non-response through these three categories, reflecting the terrain and priorities of the SPARK program and IBP more broadly. Looking at RRA in the context of this PFM map offers key insights for the twin tasks of tracing and unblocking bottlenecks in resource management systems that hinder responsiveness and accountability, as well as demanding specific reforms that make the fiscal governance system more open to citizen engagement; and · discusses how the RRA framework can be used to take stock of partial or incremental responses and assess whether change is moving towards accountable governance, by reference to the SPARK program and other IBP efforts. The RRA framework supports accountability-claiming practice by facilitating close attention to the actions of and influences on key government stakeholders, careful interpretation of these, and consequential adjustments to advocacy strategies. Its implications for monitoring, evaluating, and learning (MEL) from practice are also significant. MEL has been evolving in the accountability field in line with the thinking and practical challenges behind the development of the RRA framework. The framework adds to a range of emerging approaches that support the application theories of change, evidence-based adaptive programming, and politically aware systems thinking in the complex task of building accountable responsiveness towards constituencies historically excluded from public goods and services, and ultimately equitable development outcomes from an intersectional perspective.
Artwork Size: 936692 Bytes
Keywords: Development studies; Public policy; Social policy